2010
DOI: 10.1143/jjap.49.071603
|View full text |Cite
|
Sign up to set email alerts
|

The Charge Transport in Organic Field-Effect Transistor as an Interface Charge Propagation: The Maxwell–Wagner Effect Model and Transmission Line Approximation

Abstract: By analyzing electric field migration in the pentacene organic field-effect transistor channel (OFET), visualized using the time-resolved microscopic optical second harmonic generation (TRM-SHG) is analyzed the propagation of injected carriers. We find that the accumulated charge propagation on the pentacene-gate insulator interface of the three-electrode system is clearly different from the drift in electric field of the two-electrode system. The propagation of injected carriers is evaluated on the basis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…The pentacene OFETs used here are used for an illustration of the NP influence on organic device properties. The experimental results are well supported by the Maxwell-Wagner model [6] analysis.…”
Section: Introductionsupporting
confidence: 71%
“…The pentacene OFETs used here are used for an illustration of the NP influence on organic device properties. The experimental results are well supported by the Maxwell-Wagner model [6] analysis.…”
Section: Introductionsupporting
confidence: 71%
“…2, the TR-EFISHG measurement showed that the holes accumulated (Q 0 s > 0) and the electric field began to decrease from 10 À6 s and to saturate after 10 À3 s, indicating that t MW < 10 À3 s. That is, the holes are injected from the Au electrode and are accumulated at the TIPS-pentacene/PI interface within a response time of 10 À3 s. The latter response time t MW corresponds to the Maxwell-Wagner effect charging time that is approximately given by holecarrier transit time across the TIPS-pentacene layer. 20,21 On the other hand, for V ¼ þ10 V, I SHG increases steeply with a time of 10 À7 s in a similar manner, but it does not change significantly in the region of t > 10 À7 s, suggesting that there is no carrier injection into TIPS-pentacene and no accumulation at the PI/TIPS-pentacene interface. That is, the electrode charges are induced on the Au and ITO electrodes with a time-constant s RC 10 À7 s in a manner similar to the process for V ¼ À10 V, but the second relaxation due to the interfacial charging is very small, i.e., Q s % 0.…”
mentioning
confidence: 85%
“…The electrons moved from the drain edge in proportional to the square root of the elapsed time. We could easily understand this square root dependence from carrier transit time, by assuming a model based on an interface charge propagation which can be described by the Maxwell-Wagner model as well as the ladder RC-circuit model, 19 where the accumulated charge propagation along the organic/gate-insulator interface is regulated by the space charge field therein. Consequently, the carrier transit time of electrons t r is given by…”
Section: Observation Of Carrier Behaviormentioning
confidence: 99%